Assesses the economic and hygienic effects of aflatoxins in some of farmed fish and shrimp - Motalebi Moghanjoughi, Abbas Ali; Sepahdari, A.; Mehrabi, M.R. (Iranian Fisheries Science Research Institute, 2016)
Acipenser stellatus and Huso huso are the most important native sturgeon species in Caspian Sea. In the present study, the impacts of various concentrations of Aflatoxin B1 (AFB1) on Beluga, Huso huso, under controlled conditions were investigated. Belugas (120±10 g) were fed diets containing 0, 25, 50, 75, and 100 ppb AFB1/kg of diet for 3 months. Results showed that various levels of AFB1 do not significantly affect the specific growth ratio (SGR) (p< 0.05) of fish in different treatments. However, weight gain and food conversion ratio (FCR) varied significantly (p< 0.05 between control and treatments with diets contaminated with 75 and 100ppb AFB1/kg after 90 days). The increase in level of AFB1 did not affect the percent of survival rate (SR) and no mortality was observed in treatments (SR=100%). Various levels of AFB1 under experimental conditions of the present study affect some growth factors, such as, weight gain and FCR but have no significant impact on SGR. Histopathological studies showed that different level of AFB1 can cause broad range of changes in liver, kidney, spleen and gills tissues, particularly at concentration of 75 and 100 ppb AFB1/kg of diets after 60 days.No tumour formation observed. With regard to toxin concentration and time of exposure to AFB1 in experimental fish, different degree of skin lesions (simple hemorrhage to progressive wounds) were observed in different parts of body especially in vent, caudal peduncle, fins, and head. "Yellow sores" on head and trunk regions are considerable and led to deterioration of appearance. Prevalence of skin lesion in different treatments was 8 -53.3 %, which after stop feeding with toxic diets, 16 – 24 % healing observed.Haematological chenges included chronic anemia and lymphocytopenia.Also nutrophilia observed with increasing of skin lesions. Meat accumulation of AFB1 in different treatments is not so considerable and harmfull for human cunsumption, but is significantly different with control fishes(P<0.01) Responses of experimental ...